Assessment of executive functions in type II diabetes patients with focus on duration of diabetes: preliminary findings of an analytical cross-sectional study - Chaudhari, Sameer; Somvanshi, Padmakar (International Journal of Research in Medical Sciences, 2023)
Background: Executive functions have been defined as one’s ability to plan, initiate, sequence, monitor, and inhibit complex behaviour. Executive functions are purportedly affected significantly in diabetes population; duration of diabetes having particularly negative impact. Present study was undertaken to determine whether executive functions are affected more in diabetic patients as compared to non-diabetics and to further assess the role duration of diabetes. Methods: In this analytical, cross-sectional study being conducted over 18 months period at a tertiary-care private teaching hospital in Central India, 148 participants (74 in diabetic & 74 in non-diabetic group) between the age of 30-60 years are enrolled. Preliminary data of 50 patients is presented here. The executive functions were assessed by using Delis-Kaplan Executive function system and participants was subjected to Trail making test, Design fluency test, Tower test and DKEF sorting test and the scores were compared between the two groups. Results: Statistically significant differences were observed for Trail making test (median value diabetic-7 vs. non-diabetic-10), Design fluency test (median value diabetic-10 vs. non-diabetic-10, the range varied significantly), Tower test (median value diabetic-5 vs. non-diabetic-9), DKEF sorting test (median value diabetic-7 vs. non-diabetic-8) and Sort recognition test (median value- diabetic-6 vs. non-diabetic-8). The duration of diabetes exhibited strong, statistically significant negative correlation with the four studied parameters and had weak, insignificant positive correlation with sort recognition DS. Conclusions: Executive functions are significantly affected in adult diabetes patients as compared to non-diabetic population and duration of diabetes has major contributory role in this affection.